PENGARUH CITRA, KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN NASABAH (Studi Empiris Pada Bank BRI Cabang Jepara Unit Pecangaan) - Ahiyd Syamsuel Bisriy, 11.05.51.0069 (Students Journal of Economic and Management, 2015)
This study takes an object in PT Bank BRI Pecangaan - Jepara. Reasons for selecting objects based research because of fluctuations (rise and fall) of new customer growth in 2010-2013. Of the phenomenon it is necessary to evidence and research to analyze the influence of image, service quality and customer value on customer satisfaction. Slovin study sample using the formula obtained by 100 respondents. sample collection method is purposive sampling from a population sample selection based on the criteria specified. Methods of data analysis using linear regression and methods of data collection using the questionnaire. The test results showed that (1) the image on customer satisfaction showed a positive and significant influence, (2) quality of service to customer satisfaction showed a positive and significant influence, (3) the value of the customer to customer satisfaction showed a positive and significant effect. Keywords: image, service quality, customer value and customer satisfaction.